The future of foreign direct investment and the multinational enterprise - Ramamurti, Ravi.; Hashai, Niron (Bingley, U.K. : Emerald, 2011)
The policy and technological context within which FDI takes place has changed dramatically in the last two decades. Countries around the world have become more open to FDI, and revolutions in information and communications technology have lowered the costs of internationalization. As a result, global FDI flows have swelled, but, just as important, the forms that it takes have become more complex. For instance, emerging markets are now spawning MNEs of their own, governments and private equity firms are engaging in FDI, global sourcing is becoming central to the strategies of many firms, and offshoring encompasses many services, including high-end R&D work. In turn, these developments are exposing the limitations of the fields theoretical foundations. This Festschrift in honour of Professor Yair Aharoni, a pioneer in the field of international business, looks at several of these new trends in FDI, what they will mean for firms and governments, and the opportunities created by these developments to enrich or extend extant theory. Contributors to the volume include the worlds leading international business scholars.
Introduction : research on FDI and MNEs in a changing world / Niron Hashai, Ravi Ramamurti -- Behavioral elements in foreign direct investment decisions / Yair Aharoni -- Bringing managers' decision models into FDI research / Timothy M. Devinney -- FDI and the role of financial market quality / Jens Forssbaeck, Lars Oxelheim -- The evolution of multinationals / Yair Aharoni, Ravi Ramamurti -- New players in FDI : sovereign wealth funds, private equity, and emerging-market multinationals / Ravi Ramamurti -- Revisiting the'modern' multinational enterprise theory : an emerging-market multinational perspective / St{u2970}hane J.G. Girod, Joshua B. Bellin -- The impact of globalisation and the emergence of the global factory / Peter J. Buckley -- Trade in services : the global sourcing of business services / Arie Y. Lewin -- The born global illusion and the regional nature of international business / Alan M. Rugman, Paloma Almod{u2BF6}ar -- Global service multinationals from a small open economy : the case of Israeli high-tech service providers / Niron Hashai -- Governance of foreign affiliates as a distinctive choice between networks, market, and hierarchy / Lilach Nachum -- Unraveling the relationships between internationalization and product diversification among the world's largest food and beverage enterprises / Niron Hashai, Tamar Almor, Marina Papanastassiou, Fragkiskos Filippaios, Ruth Rama -- The impact of foreign direct investment on local firms : western firms in emerging markets / Pervez N. Ghauri, Rebecca Firth -- If Teva changes its'nationality,' would Israel's economy be affected? / Seev Hirsch -- The regulatory framework for investment : where are we headed? / Karl P. Sauvant.
Includes index.
Keywords: Investments, Foreign; Investments, Foreign -- Forecasting